2014
DOI: 10.1002/eco.1582
|View full text |Cite
|
Sign up to set email alerts
|

Size and connectivity of upslope runoff‐source areas modulate the performance of woody plants in Mediterranean drylands

Abstract: Feedbacks between vegetation spatial pattern and resource redistribution from bare areas (sources) to vegetation patches (sinks) are considered critical to the functioning of dryland ecosystems. However, experimental fieldworks testing the underlying assumptions and quantifying the feedbacks involved are very scarce. We hypothesized that the size and surface conditions of the upslope runoff‐source areas control the transfer of resources to the downslope vegetation patch, and thereby vegetation performance. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 59 publications
2
19
0
Order By: Relevance
“…Besides plant cover, plant pattern is also important for soil and water conservation (Ludwig et al ; Bautista et al ). It refers to the spatial arrangement of run‐on, that is, patches, and runoff zones, that is, inter‐patches, which together form functional units (Tongway & Hindley ; Urgeghe & Bautista ). Larger patch cover and width, and therefore larger areas with resource sink capacity (Ludwig & Tongway ), were found in moderate grazing, no grazing and full reforestation, in the latter case probably because of the contribution of the banks and troughs created along the contours.…”
Section: Discussionsupporting
confidence: 94%
“…Besides plant cover, plant pattern is also important for soil and water conservation (Ludwig et al ; Bautista et al ). It refers to the spatial arrangement of run‐on, that is, patches, and runoff zones, that is, inter‐patches, which together form functional units (Tongway & Hindley ; Urgeghe & Bautista ). Larger patch cover and width, and therefore larger areas with resource sink capacity (Ludwig & Tongway ), were found in moderate grazing, no grazing and full reforestation, in the latter case probably because of the contribution of the banks and troughs created along the contours.…”
Section: Discussionsupporting
confidence: 94%
“…Urgeghe et al (2010) reported that the collection of runoff by herbaceous patches in a dryland pinyon-juniper ecosystem in southwest USA was maximum when both interpatch bare soil and herbaceous cover were intermediate, suggesting a trade-off between source and sink areas at the finer scale and the existence of herbaceous cover thresholds at the broader catchment scale. Some properties of the sink/source pattern, such as the upslope length and the size of the source area, have been successfully related to the performance of planted seedlings in drylands' restoration actions (Urgeghe and Bautista, 2015). Landscape Function Analysis (LFA) (Tonway and Hindley, 2004) incorporates both vegetation and soil survey in the evaluation of dryland patchy ecosystems, using functional indicators instead of direct measures of key features.…”
Section: Functional Approaches In the Monitoring Of Dryland Ecosystemmentioning
confidence: 99%
“…Both issues are highly dependent on horizontal water redistribution at the patch to landscape scales (Breshears et al 1997, Davenport et al 1998, and can be affected intentionally or non-intentionally by the management of livestock grazing and associated trampling and soil compaction (George et al 2004). Recent research on water redistribution processes has focused on the effects of canopy architecture, spatial distribution of vegetation, ecosystem connectivity, and soil infiltration rate (Newman et al 2010, Ravi et al 2010, Villegas et al 2010, Urgeghe and Bautista 2014, Okin et al 2015. Notably, in these and other studies, rainfall has been typically characterized only by event size, largely due to the availability of historical daily aggregated data.…”
Section: Introductionmentioning
confidence: 99%